Peran Cyanobacteria terhadap Oksigenasi Bumi dan Evolusi Kloroplas - Allifa Khoerurrahmah; Alvi Arumi Fadila; Lindiyani Lindiyani; Muhimatul Umami (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Cyanobacteria play an important role in the evolution of the earth and biosphere. Cyanobacteria play a role in the oxygenation of the atmosphere and oceans that began since the great oxidation event. These living things are the main producers in the ocean in the past and present and are the ancestors of Chloroplasts. The morphology commonly used is still difficult to read for microfossil interpretation which makes the identification of cyanobacteria in the early fossil record still ambiguous. This study was conducted to review classical and new cyanobacterial biosignatures. In addition, this study will also analyze the fossil record of cyanobacteria mentioned earlier and the challenges of molecular approaches to modern cyanobacteria. The suggestions we provide are new calibration points for molecular clocks and strategies to increase insight into the timing and patterns of cyanobacteria evolution and oxygenic photosynthesis.